Design and construction of a flexible laboratory-scale mixing apparatus for continuous ethylene supplementation of fresh produce - Amoah, Robert S.; Landahl, Sandra; Terry, Leon A. (Elsevier, 2017)
The design and construction of a laboratory-scale apparatus for generating variable concentrations and flow rates of exogenous ethylene for fresh produce supplementation during storage trials is described. A stock of compressed ethylene in nitrogen (5000 μl l−1) was blended into a continuous flow stream of air and diluted to the desired concentrations. The ethylene and air flow rates were controlled with calibrated mass flow control valves. An empirical mathematical model was derived for real-time variation of both the mixed concentration and flow rate during continuous flow. Validation of the model was performed using fresh sweet potato as a case study where a steady continuous ethylene concentration of 10 μl l−1 was achieved for three months. The bespoke system offers easy-to-manage ethylene supplementation for research.
Keywords: Ethylene blending; Controlled atmosphere; Mass flow controller; Fresh produce; Storage